Effects of Arum dioscoridis Extract on Hepatic Toxicity Caused by Thioacetamide in Rats - Sökmen, Murat Fatih; İspiroğlu, Murat; Gişi, Kadir; Bahar, Abdulkadir Yasir; Belge Kurutaş, Ergül; Kantarçeken, Bülent (Turkish Journal of Gastroenterology, 2023)
Background: The aim of this study was to investigate the prophylactic and therapeutic effects of Arum dioscoridis (tirsik) plant extract against thioacetamide-induced experimental liver toxicity.Methods: In this study, 35 male Wistar–Albino rats, of 12-14 weeks old, weighing between 200 and 270 g, were used. Rats were divided into 5 groups of 7 each. The first group was determined as the control group, the second group as the hepatotoxicity group, the third group as the prophylaxis group, the fourth group as the intraperitoneal treatment group, and the fifth group as the oral treatment group. Hepatotoxicity was achieved with a single intraperitoneal dose of 350 mg/kg of thioacetamide (TAA). On the seventh day, the rats were sacrificed under general anesthesia. Their blood was taken and liver enzymes were studied. Malondialdehyde (MDA), glutathyon peroxidase (GPx), catalase (CAT), superoxit dismutase (SOD) enzymes were studied from liver tissues. In addition, liver tissues were evaluated histopathologically.Results: With Arum dioscoridis treatment and prophylaxis, improvements in all parameters and increases in tissue antioxidant levels were detected.Conclusion: It was determined that Arum dioscoridis plant extract has prophylactic and therapeutic effects on liver toxicity. In cases of acute liver injury and hepatotoxicity, we suggest the potential application of Arum dioscoridis for effective and inexpensive treatment.Cite this article as: Sökmen MF, İspiroğlu M, Gişi K, Bahar AY, Kurutaş EB, Kantarçeken B. Effects of Arum dioscoridis extract on hepatic toxicity caused by thioacetamide in rats. Turk J Gastroenterol. 2023;34(3):254-261.